Complete genome sequence of Mesorhizobium ciceri Strain R30, a Rhizobium used as a commercial inoculant for Chickpea in Argentina - Foresto, Emiliano (2022)
We report the complete genome sequence of Mesorhizobium ciceri strain R30, a rhizobium strain recommended and used as a commercial inoculant for chickpea in Argentina. The genome consists of almost 7 Mb, distributed into two circular replicons: a chromosome of 6.49 Mb and a plasmid of 0.46 Mb.